PENGARUH KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR AKUNTANSI KEUANGAN SISWA KELAS XI DI SMK NEGERI 5 PALEMBANG TAHUN PELAJARAN 2015/2016 - Yesi Ike; Riswan Jaenudin; Ikbal Barlian (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2016)
This study was aimed to prove: The Effect of emotional intelligence towards students’ finacial accounting achievment of eleventh graders of vocational school numbers 5 Palembang academic year 2015/2016. This study was a causal associative study. The population was the elevent grade students of eccounting major of vocational school number 5 palembang academik year 2015/2016 who belong to three diffrent classes with 122 student as the total number. To choose the sample, random sampling technique was used, so there were 61 students as the sample. In collecting the data, questionnaire and documentation were used. Based on the result, the emotional intelligence of the eleventh grade students manjoring accounting was 63,93% which was in a moderate category. Statistically, the result showed that F calculate ≥ F table ( 18,77 ≥ 4,00) which meansh that there was a significant correlation between emotional intelligence an students’ finacial accounting achievement. The writer hopen that this study might encourage onther writers to figure out onother factor which influences the students’ finacial accounting achievement.